THE PROOFING OF THE CRIME OF SPREADING HOAX NEWS IN THE INVESTIGATION STAGE - dimas bagus lisdiyantoro; misbakhul munir; Dia Ayu Milatina (Journal Philosophy of Law, 2021)
To control the crime of spreading hoax news, the government has made and updated Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions in the Law. It will be enforced with Article 45 A paragraph (1). The formulation of the problem in this study is 1) How is the implementation of investigations against perpetrators of hoax news spreaders who cause trouble among the community 2) What are the obstacles for investigators in uncovering cases related to evidence of violations of the Electronic Information and Transactions (ITE) Law on hoax news? The research method used is juridical empirical. This approach means that the study of research data is guided by the law of proving the spread of hoax news. The results of this study concluded that 1) Implementation of investigations against perpetrators of hoax news spreaders who are perpetrators of criminal acts of information and electronic transactions that cause trouble in the community with evidence of hoax news spreading by tracing users of hoax news spreading accounts following Article 28 paragraph (1) of Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions. 2) Obstacles of investigators in uncovering cases related to evidence of a violation of the ITE Law on Hoax News a) Evidence of crime from computer equipment, mobile phones, and various electronic media that can access the internet can be easily destroyed or removed; b) The suspect gave convoluted information; c) Cases of violations of the ITE Law are carried out with groups or individuals whose average perpetrators are still young in their activities and sometimes have networks outside the city; d) In general, the perpetrators have many fictional accounts created regarding violations of the ITE Law; e) Inadequate facilities and infrastructure of officers in conducting investigations.